2020
DOI: 10.1074/jbc.ra120.014183
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 3 modulates the renin–angiotensin system in mice

Abstract: Dipeptidyl peptidase 3 (DPP3) is a zinc-dependent hydrolase involved in degrading oligopeptides with 4–12 amino acid residues. It has been associated with several pathophysiological processes, including blood pressure regulation, pain signaling, and cancer cell defense against oxidative stress. However, the physiological substrates and the cellular pathways that are potentially targeted by DPP3 to mediate these effects remain unknown. Here, we show that global DPP3 deficiency in mice (DPP3-/-) affects the reni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…DPP3 is a zinc-dependent metalloprotease that cleaves the N-terminal extremity of various bioactive peptides, including angiotensins, enkephalins, and endorphins ( 4 ). Interestingly, although DPP3 hydrolyzes angiotensin II into angiotensin IV, it has no direct effect on angiotensin I, thus leading to an increased angiotensin I/angiotensin II ratio, consistent with Bellomo and colleagues’ findings ( 5 , 6 ). Under these conditions, as pointed out by the authors, decreased AT1R stimulation then triggers the production of renin.…”
supporting
confidence: 90%
“…DPP3 is a zinc-dependent metalloprotease that cleaves the N-terminal extremity of various bioactive peptides, including angiotensins, enkephalins, and endorphins ( 4 ). Interestingly, although DPP3 hydrolyzes angiotensin II into angiotensin IV, it has no direct effect on angiotensin I, thus leading to an increased angiotensin I/angiotensin II ratio, consistent with Bellomo and colleagues’ findings ( 5 , 6 ). Under these conditions, as pointed out by the authors, decreased AT1R stimulation then triggers the production of renin.…”
supporting
confidence: 90%
“…Multiple studies had already pointed out the putative rapid angiotensin-scavenging properties of DPP3 based on in vitro experiments [18]. Angiotensin II, angiotensin III, angiotensin IV, angiotensin 1-5 and angiotensin 1-7 were all found to be effectively hydrolysed by DPP3 [17,18,44], with angiotensin IV (six amino acids in length) being hydrolysed ten times faster than angiotensin II (eight amino acids in length) [21]. However, as reliable assays to measure cDPP3 were not available, these findings could not be confirmed in vivo.…”
Section: Dpp3 As a Depressant Of The Cardiovascular Systemmentioning
confidence: 99%
“…Of note, DPP3 infusion reduced circulating angiotensin II levels to even lower levels than baseline, suggesting that endogenously produced angiotensin II was also effectively cleaved. In DPP3 (À/À) knockout mice, significant upregulation of the classical RAAS was observed, reflected by higher circulating levels of angiotensin II, angiotensin III, angiotensin IV and angiotensin 1-5, all known substrates of DPP3 [17].…”
Section: Dpp3 Administration and Dpp3 Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Recently, in vivo studies reported that global DPP3 deficiency in mice affects the concentrations of the renin-angiotensin-aldosterone system (RAAS) peptides strengthening previous findings showing a constitutive presence of DPP3 in healthy human blood. 21,22 In disease, high plasma circulating DPP3 (cDPP3) levels have been found in sepsis, cardiogenic shock and vasodilatory shock, where cDPP3 is associated with organ failure and mortality. 22,23 Adrenomedullin (ADM) is a 52-amino acid peptide with vasoactive properties and expressed in numerous tissues.…”
Section: Introductionmentioning
confidence: 99%